HASIL PENGGUNAAN BUKU NETZWERK A2 TERHADAP KETERAMPILAN MEMBACA SISWA KELAS X SMA NEGERI 1 TAMAN - Wiryayasa, I Made Dwi Wahyu Krisna; Pujosusanto, Ari (LATERNE, 2022)
Language is an ability that must be mastered to communicate. According to Tarigan (2015: 10) good reading skills are a support for success in other things. Nutall (2008: 11) also stated that reading is part of the reading comprehension process. The formulation of the problem in this research, namely: 1) how are the learning outcomes of using Netzwerk in German reading skills? 2) how are the learning outcomes of using Deutsch ist einfach in German reading skills? 3) how do the learning outcomes of German reading skills compare with the use of Netzwerk and Deutsch ist einfach? The objectives of this research are 1) to determine the learning outcomes of using the Netzwerk in German reading skills, 2) to determine the learning outcomes of using the Deutsch ist einfach in German reading skills, and 3) to compare the results of learning reading skills in German. Germany against the use of the Netzwerk and Deutsch books ist einfach. The average results of the pretest and posttest obtained in the experimental class, namely 76.29 and 94.6 with the average difference between the two results is 18.31. In the control class, the average pretest was 66.57 and posttest of 77 with an average difference of 10.43. By comparing the average results of the experimental class posttest and the control class obtained an average difference of posttests of the two classes of 17.6. This indicates that the average posttest value of the experimental class is greater than the control class. Then it can be concluded that 1) the use of Netzwerk learning books in learning has a significant good impact on the learning outcomes of reading skills in German subjects class X SMAN 1 Taman; 2) the use of Deutsch ist einfach learning books in teaching and learning activities has a good impact on the learning outcomes of german reading skills class X SMAN 1 Taman; 3) Comparison of the results of learning German reading skills between class X MIPA 1 and X Bahasa obtained the result that the use of Netzwerk learning books applied to experimental classes obtained greater results than the use of learning books Deutsch ist einfach.